The return of Hans Staden : a go-between in the Atlantic world - Duffy, Eve M. (Johns Hopkins University Press, 2012)
Hans Staden's sixteenth-century account of shipwreck and captivity by the Tupinambá Indians of Brazil was an early modern bestseller. This retelling of the German sailor's eyewitness account known as the True History shows both why it was so popular at the time and why it remains an important tool for understanding the opening of the Atlantic world. Eve M. Duffy and Alida C. Metcalf carefully reconstruct Staden's life as a German soldier, his two expeditions to the Americas, and his subsequent shipwreck, captivity, brush with cannibalism, escape, and return. The authors explore how these events and experiences were recreated in the text and images of the True History. Focusing on Staden's multiple roles as a go-between, Duffy and Metcalf address many of the issues that emerge when cultures come into contact and conflict. An artful and accessible interpretation, The Return of Hans Staden takes a text best known for its sensational tale of cannibalism and shows how it can be reinterpreted as a window into the precariousness of lives on both sides of early modern encounters, when such issues as truth and lying, violence, religious belief, and cultural difference were key to the formation of the Atlantic world.